Pengembangan Media Pembelajaran Modul Elektronik (E-Modul) Menggunakan Google Site pada Mata Pelajaran TIK di MA Al Fattahiyyah - Fika Nailul Muna; Fahrur Rozi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Electronic modules (E-modules) are a set of digital learning media that are systematically designed to support independent learning. E-modules can be used as a complement to teaching materials in learning activities, especially in the application of electronic-based media. The purpose of this study is to develop e-module learning media in Google Site-based ICT subjects that are suitable for use at MA Al Fattahiyyah Tulungagung. This research uses a research and development approach (Research and Development) with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model. The material developed in the e-module is adjusted to the MA Al Fattahiyyah class X syllabus, especially the material